Survey on Surging Technology: Cryptocurrency - Singh, Swathi; R, Suguna; Satish, Divya; Kumar MV, Ranjith (International Journal of Engineering and Technology, 2018)
The paper gives an insight on cryptography within digital money used in electronic commerce. The combination of digital currencies with cryptography is named as cryptocurrencies or cryptocoins. Though this technique came into existence years ago, it is bound to have a great future due to its flexibility and very less or nil transaction costs. The concept of cryptocurrency is not new in digital world and is already gaining subtle importance in electronic commerce market. This technology can bring down various risks that may have occurred in usage of physical currencies. The transaction of cryptocurrencies are protected with strong cryptographic hash functions that ensure the safe sending and receiving of assets within the transaction chain or blockchain in a Peer-to-Peer network. The paper discusses the merits and demerits of this technology with a wide range of applications that use cryptocurrency.
Keywords: Blockchain; Cryptocurrency.